Next-generation Tumor-homing Induced Neural Stem Cells as an Adjuvant to Radiation for the Treatment of Metastatic Lung Cancer - Alison R. Mercer-Smith; Andrew Buckley; Alain Valdivia; Wulin Jiang; Morrent Thang; Noah Bell; Rashmi J. Kumar; Hunter N. Bomba; Alex S. Woodell; Jie Luo; Scott R. Floyd; Shawn D. Hingtgen (Stem Cell Reviews and Reports, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Intravenously Infused Stem Cells for Cancer Treatment - Alison R. Mercer-Smith; Ingrid A. Findlay; Hunter N. Bomba; Shawn D. Hingtgen (Stem Cell Reviews and Reports, 2021)

Changes in responsiveness to allatostatin treatment accompany shifts in stress reactivity in young worker honey bees - Elodie Urlacher; Jean-Marc Devaud; Alison R. Mercer (Journal of Comparative Physiology A, 2019)

Measurements of Chlorpyrifos Levels in Forager Bees and Comparison with Levels that Disrupt Honey Bee Odor-Mediated Learning Under Laboratory Conditions - Elodie Urlacher; Coline Monchanin; Coraline Rivière; Freddie-Jeanne Richard; Christie Lombardi; Sue Michelsen-Heath; Kimberly J. Hageman; Alison R. Mercer (Journal of Chemical Ecology, 2016)

The New Zealand experience of varroa invasion highlights research opportunities for Australia - Jay M. Iwasaki; Barbara I. P. Barratt; Janice M. Lord; Alison R. Mercer; Katharine J. M. Dickinson (Ambio, 2015)

The power of comparison - Bing Zhang; Alison R. Mercer (Journal of Comparative Physiology A, 2015)

Age- and behaviour-related changes in the expression of biogenic amine receptor genes in the antennae of honey bees (Apis mellifera) - Henry J. McQuillan; Andrew B. Barron; Alison R. Mercer (Journal of Comparative Physiology A, 2012)

Modulatory actions of dopamine and serotonin on insect antennal lobe neurons: insights from studies in vitro - Charles W. Ellen; Alison R. Mercer (Journal of Molecular Histology, 2012)

Manipulating the light/dark cycle: effects on dopamine levels in optic lobes of the honey bee (Apis mellifera) brain - Elizabeth Carrington; Ilona C. Kokay; Jane Duthie; Robert Lewis; Alison R. Mercer (Journal of Comparative Physiology A, 2007)